The Impact of Generative AI on Clinical Decision-Support Systems: A Systematic Review of Applications, Benefits, and Ethical Challenges - Polampally, Sanjay Kumar; Ravindran, Renjith Kathalikkattil; Jeyabalan, Jeyashree; Kusam, Venugopala Reddy; Morsu, Ashok; Ragunayakula, Sharat Kumar (Proceedings of Universitas Muhammadiyah Yogyakarta Graduate Conference, 2025)
This systematic literature review explores the integrations of generative artificial intelligence (AI) models, such as ChatGPT, GPT-4, MedPaLM, BioGPT, and LLaMA, into Clinical Decision Support Systems (CDSS) between 2020 and 2025. Analyzing 500 studies across multiple countries and healthcare contexts, the paper evaluates that generative AI transforms clinical workflows through enhanced diagnostic assistance, personalized treatment planning, improved patient communication, and document automation."This systematic literature review provides the first comprehensive analysis of generative artificial intelligence (AI) integration into Clinical Decision Support Systems (CDSS) from 2020 to 2025, addressing a critical gap in understanding their transformative impact on healthcare delivery. Through rigorous PRISMA-guided analysis of 500 peer-reviewed studies across six continents, we establish a novel theoretical framework demonstrating how generative AI models (ChatGPT, GPT-4, MedPaLM, BioGPT, and LLaMA) fundamentally reshape clinical workflows through four primary mechanisms: enhanced diagnostic reasoning, personalized treatment optimization, adaptive patient communication, and intelligent documentation automation.